(untitled) (Bucharest Working Papers in Linguistics, 2025)
The goal of this paper is to provide a short state of the art review of third language (L3) acquisition research from a generative point of view . I present som e of the most important theoretical models of morphosyntactic transfer along with the results of exemplar studies that test them. R esearch in this field of study is most interested in tracing transfer, identifying its source(s) first language (L1 and/or second language ( L2 and determining its nature facilitative or non facilitative in the process of a ttaining proficiency in L3 see Rothman et al. 2019). Experimental results indicate that both previously acquired languages (L1 and L2) can be transfer red in a facilitative and non facilitative manner , approving or contradicting some of the proposed models of transfer. I conclude that there is a need for more research, testing the models across different language combinations and thus providing answers t o the questions raised by th e field.